If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4 = x + 7 Combine like terms: 3 + 4 = 7 7 = x + 7 Reorder the terms: 7 = 7 + x Add '-7' to each side of the equation. 7 + -7 = 7 + -7 + x Combine like terms: 7 + -7 = 0 0 = 7 + -7 + x Combine like terms: 7 + -7 = 0 0 = 0 + x 0 = x Solving 0 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 0 + -1x = x + -1x Remove the zero: -1x = x + -1x Combine like terms: x + -1x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 9x(x-5)(2x+3)=0 | | -17x^2-27x+4=0 | | y=-(x+1)(2)-8 | | j=3k-5 | | 3x^2+3y^2+3x-12=-1 | | 5x-162=0 | | 5x-2(1-2x)=14 | | 3x-32=61 | | log(5x+4)=log^6 | | f(4)=6(4)+7 | | -37+4x=23-x | | 7=n+18 | | 5x-22/2=x+31 | | 3=4-3 | | 10(-5+7)-3=17 | | 3x-5(x-4)=-9+5-6 | | 3x-12=2x+9 | | 5(3p-7)+25=35 | | 22=4x+2(2x-9) | | -7+2x=7+4x | | (t+10)+(t+20)+t=360 | | -7=5v+8 | | x+31=x | | 5x-5=4x+17 | | -38=-3+5w | | 21=2x+7 | | 2.4-x=x-5.6 | | 57=3w | | 6.8a+13=74.2 | | 21x^3-7x=0 | | 6x-51=13-2x | | 17x-6=11x-18 |